Profile of Transepidermal Water Loss in Non-Atopic Dermatitis and Atopic Dermatitis in Indonesian Adults - Damayanti; Anggraeni, Sylvia; Ayu Umborowati, Menul; Farah Adiba, Asmahan; Prakoeswa, Cita Rosita Sigit (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Atopic dermatitis (AD) is a recurrent and chronic inflammatory skin disease affecting the quality of life and productivity of individuals. Several studies have reported the profile of transepidermal water loss (TEWL) in AD patients, however, there is either no data or very limited data on TEWL values in normal skin or in non-atopic individuals. Purpose: This study aims to update of the available evidence about TEWL values in healthy (non-AD) adults and AD patients, especially in Indonesia. Methods: This analytic study involved 37 non-AD subjects and 37 subjects with AD. TEWL measurements were assessed on the volar side of the left forearm. Result: The mean values in the non-AD group were 5.61 ± 3.85, while the mean values in the AD group were 18.07 ± 4.88. There is a significant difference in TEWL ​​values between the groups with non-atopic dermatitis and atopic dermatitis (p<0.001). Conclusion: TEWL value is significantly higher in AD patients compared to non-AD  individuals, indicating a compromised skin barrier function in AD. The consistent results across populations and geographic regions support the utility of TEWS as a reliable measure of AD severity, which can help clinicians customize treatment plans to meet the needs of each patient.